The unsteady eye: an information-processing stage, not a bug. Issue 4 (April 2015) - Rucci, Michele; Victor, Jonathan D.
Highlights Small eye movements are always present during natural visual fixation. Fixational movements do not merely prevent the image from fading, they reformat it. Fixational modulations eliminate correlations before neural processing. Fixational modulations enhance high spatial frequencies and begin edge extraction. Spatial representations are intrinsically sensorimotor starting from the retina.